Partner Satisfaction With The Implementation of The Cooperation Information System (Sikerja) at Aji Muhammad Parikesit Regional Hospital - Muhammad Henrie Irawan; Mardiana Widya Utami; Aulia Rizki Nur Safitri; Sonny Santoso; Sutag Harsie (Griya Eka Sejahtera, 2026)
Background: Managing cooperation agreements in hospitals requires an efficient and transparent process. Aji Muhammad Parikesit Regional General Hospital implemented the Cooperation Information System (SIKERJA) to optimize the cooperation agreement process, which previously took 2,028 minutes to 110 minutes. The purpose of the study was to analyze the level of satisfaction of cooperation partners with the implementation of SIKERJA and its impact on operational efficiency at Aji Muhammad Parikesit Regional General Hospital.Methods: Quantitative descriptive research with a cross-sectional design. The research sample consisted of 35 respondents (60% internal employees and 40% external partners) selected using purposive sampling. Data collection using a structured questionnaire with a Likert scale. Data analysis using descriptive statistics.Results: User satisfaction reached 96.25 % , with details: ease of use 97%, process speed 96%, flow clarity 94%, and data accuracy 98%. The implementation of SIKERJA successfully reduced process cycle time by 94.6 % , saved paper usage 90%, and reduced meeting costs by 77.8%. The number of cooperation agreements increased from 12 to 28 cases in 6 months (a growth of 133%).Conclusion: The implementation of SIKERJA was highly effective in improving partner satisfaction and operational efficiency. This system can serve as a best practice for replication in other healthcare institutions